Open versus Thoracoscopic RFA-Assisted Lung Resection. (2nd November 2017) - Poupalou, Anna; Kontos, Michael; Felekouras, Evangelos; Papalois, Apostolos; Kavantzas, Nikolaos; Agrogiannis, George; Yagoubi, Fatima; Tomos, Periklis
ABSTRACT: The purpose of this study was to evaluate Radio Frequency Ablation (RFA)-assisted lung parenchymal transection through thoracotomy and thoracoscopy. Twelve domestic pigs underwent RFA-assisted lingulectomy: six through thoracotomy (group A), and six with thoracoscopy (group B). There was no mortality, no bleeding, or air leak intra- or postoperatively in either of the groups, and no conversion to open thoracotomy in group B. Group A had longer operating period and more pleural adhesions. A barotrauma, a skin burn, and a localized infection were observed in this group. Histopathology confirmed a sharply demarcated area of coagulation necrosis without damage to adjacent structures. RFA-assisted lung resection through thoracotomy bears the inherent problems of an open approach, and the use of RFA device does not add to morbidity. The thoracoscopic use of RFA probe by experienced surgeons is considered safe, maintaining the advantages of key-hole surgery.